2005
DOI: 10.1111/j.1461-9555.2005.00246.x
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of consumption of corn pollen by the predator Coleomegilla maculata (Coleoptera: Coccinellidae) during anthesis in an Illinois cornfield

Abstract: 1 Coleomegilla maculata DeGeer feeds on corn pollen in the field, but the degree to which this predator relies on corn pollen as part of its diet is not well understood. We quantified the amount of pollen consumed by C. maculata second, third and fourth instars and adults in the field. 2 Laboratory experiments were conducted to determine the digestion rate and duration of different stadia or stages using temperature regimens that reflected field conditions during anthesis. Coleomegilla maculata larvae and adul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
41
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 43 publications
1
41
0
1
Order By: Relevance
“…This result corroborates those of Smith (1965) and Lundgren et al (2005), who observed that larvae of C. maculata also ingest pollen grains, not only the adults. This result also indicates that this lady beetle species accepted the pollen grains of the three species as food, however, more studies are needed to conclude if this food is adequate to guarantee its survival and reproduction, preferentially leading to longer lifespan of adults and fecundity, or whether it is simply a complementary food source that would only warrant its survival, as was pointed out by Almeida and Ribeiro-Costa (2009).…”
Section: Ingestion Of Pollens By C Maculatasupporting
confidence: 91%
See 3 more Smart Citations
“…This result corroborates those of Smith (1965) and Lundgren et al (2005), who observed that larvae of C. maculata also ingest pollen grains, not only the adults. This result also indicates that this lady beetle species accepted the pollen grains of the three species as food, however, more studies are needed to conclude if this food is adequate to guarantee its survival and reproduction, preferentially leading to longer lifespan of adults and fecundity, or whether it is simply a complementary food source that would only warrant its survival, as was pointed out by Almeida and Ribeiro-Costa (2009).…”
Section: Ingestion Of Pollens By C Maculatasupporting
confidence: 91%
“…However, Lundgren et al (2005) estimated that the consumption of corn pollen grains (Z. mays) by fourth instar larvae of C. maculata was of 3.30 mg and the adults consumed 13.15 mg of pollen of this Poaceae during the period of anthesis in transgenic corn crops in Illinois, USA, without mentioning what this represents in terms of the number of ingested pollen grains. Dupuis et al (1987) estimated that 2500 Z. mays pollen grains in one milligram, therefore, considering only the consumption of fourth instar larvae and of adults of C. maculata recorded by Lundgren et al (2005), would give a total of 41125 pollen grains. Therefore, it gives a quantity relatively higher than the consumption of Apiaceae grains by these phases in the present study, reaching a peak of 14.94% greater than the dill grains.…”
Section: Ingestion Of Pollens By C Maculatamentioning
confidence: 99%
See 2 more Smart Citations
“…It is a natural enemy of aphids, mites, and eggs and larvae of coleopterans and lepidopterans (Hodek 1973, Weeden et al 2007, and also feeds on pollen and nectar to survive periods when prey is scarce (Hodek & Honek 1996, Lundgren et al 2004.…”
Section: Introductionmentioning
confidence: 99%